2006
DOI: 10.1143/jjap.45.4703
|View full text |Cite
|
Sign up to set email alerts
|

Transducer Vibration Method for Interference-Based Reflection-Type In Vivo Measurement for Acoustic Impedance of Bone

Abstract: In this paper, we describe about a transducer vibration method for the measurement of acoustic impedance of bone, which enables to shorten the time of measurement without binding the patient. In the interference-based reflection-type measurement method, body motion is a problem; therefore, it is desirable to complete measurement in a short time. In addition, to eliminate the effect of motion, the part of the body to be measured is usually bound firmly. However, considering the burden on the subject, this is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…The principle of the interference-based reflection-type acoustic impedance measurement method has already been reported [5][6][7][8]. An outline of the method is shown in Fig.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The principle of the interference-based reflection-type acoustic impedance measurement method has already been reported [5][6][7][8]. An outline of the method is shown in Fig.…”
Section: Theorymentioning
confidence: 99%
“…The minimum amplitude is calculated from the average and maximum amplitudes [7,8]. Therefore, using the top cover to eliminate the change in distance between the tip of the rod and the material, the change in the interference signal between the reflected wave from the rod and that from the surface of the sample is dependent on the maximum amplitude alone, as Fig.…”
Section: Theorymentioning
confidence: 99%
“…This is particularly true if the vibration is being transferred between media of widely differing physical properties such as air to solid or vice versa. As an illustration, the characteristic impedance of air is 407 N s/m 3 , that of water is 1.5610 6 N s/m 3 [33], and that of bone is 2.4610 6 N s/m 3 [34]. This causes a greater problem at higher frequencies, which is, unfortunately, where the majority of people have their hearing loss.…”
Section: Hearing-aid Designmentioning
confidence: 99%
“…T he propagation of ultrasound in bones has been an important subject of research because of its relevance to clinical applications, in particular to the ultrasonic diagnosis of osteoporosis. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Compared with radiological (X-ray) methods, ultrasonic measurement has advantages such as being free from radiation exposure and its instrumental compactness. In addition, since the propagation of ultrasound is directly affected by the elastic properties of the medium such as stiffness or mass density, ultrasonic methods are expected to characterize the mechanical deterioration of bones that leads to fractures more precisely.…”
mentioning
confidence: 99%
“…In most experimental studies previously reported, [2][3][4][5][6][7][8][9][10][11][12] ultrasonic waveforms in the time domain, and thus in the frequency domain, have been the main target of analysis, and less attention has been paid to the spatial distribution of the ultrasonic field. Since human bones have such complicated structures as nonuniformly rounded surfaces (cortical bones) and inner trabecular networks (cancellous bones), we cannot expect the ultrasonic transmission in bones to be a simple process.…”
mentioning
confidence: 99%